New and little known species of the Orphninae (Coleoptera: Scarabaeidae) from Madagascar - Frolov, Andrey V.; Akhmetova, Lilia A. (Zootaxa, 2019)
Two new species of the orphnine scarab beetle genus Madecorphnus Paulian, 1992 are described: M. heidiae Frolov & Akhmetova, new species, and M. ranomafanensis Frolov & Akhmetova, new species, from the Ranomafana National Park, Fianarantsoa Province, Eastern Madagascar. The new species can be easily distinguished by the endophallic armature consisting of more than 10 small and similar, conical tubercles in the former species and 3 long sclerites and 2 smaller indistinctly separated clusters of robust spinules in the later. Exact locality data are provided for the first time for two Triodontus Westwood, 1845, species: T. hildebrandtii (Fairmaire, 1883) was found in the northern Madagascar and is probably endemic to the Amber Mountain Range, T. fairmairei Frolov, Montreuil & Akhmetova, 2016, was also found in the northern Madagascar: Antsiranana Province, Djangoa. The updated key to the Madecorphnus species is given.